2023
DOI: 10.3390/biomimetics8020244
|View full text |Cite
|
Sign up to set email alerts
|

Finger Kinematics during Human Hand Grip and Release

Abstract: A bionic robotic hand can perform many movements similar to a human hand. However, there is still a significant gap in manipulation between robot and human hands. It is necessary to understand the finger kinematics and motion patterns of human hands to improve the performance of robotic hands. This study aimed to comprehensively investigate normal hand motion patterns by evaluating the kinematics of hand grip and release in healthy individuals. The data corresponding to rapid grip and release were collected fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The resulting ROM is compared with human data as presented in Table 2 , where the positive direction is calculated from the indicated direction. The dynamic ROM of human fingers is tested in a continuous motion over 5 s, with data calculated from [ 28 ]. Compared to the dynamic ROM of a human finger, our robot has a ROM of 113%, 87% and 88%, respectively, for the DIP, PIP and MCP joints.…”
Section: Evaluation Of Biomimetic Functionsmentioning
confidence: 99%
“…The resulting ROM is compared with human data as presented in Table 2 , where the positive direction is calculated from the indicated direction. The dynamic ROM of human fingers is tested in a continuous motion over 5 s, with data calculated from [ 28 ]. Compared to the dynamic ROM of a human finger, our robot has a ROM of 113%, 87% and 88%, respectively, for the DIP, PIP and MCP joints.…”
Section: Evaluation Of Biomimetic Functionsmentioning
confidence: 99%
“…Previous studies related to hand anatomy and kinematics have shown that flexor muscles located on the fingers and palm are responsible for the flexion of the wrist and fingers. Not surprisingly, those muscles have an important effect on the grip strength of fingers and palm [21][22][23][24]. According to previous kinematic studies, hand grasp motion is divided primarily into power, precision, and intermediate (optional) grasps [25][26][27].…”
Section: Finger Flexion In Grip-lift Interactionsmentioning
confidence: 99%
“…Therefore, EMG-controlled prostheses are popular today, which incorporate embedded motors that move the fingers based on recorded electrical activities during muscle contractions that come from the patient's brain [5]. These prostheses allow for multiple grip patterns and user-friendly interaction [6]. However, a major challenge with EMG prosthetics is that it takes users many months of continuous training to achieve full mastery over EMG-controlled prosthetics [7].…”
Section: Introductionmentioning
confidence: 99%